2022
DOI: 10.1371/journal.pone.0273791
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endophytic colonization by entomopathogenic fungi on the behavior and life history of the tobacco peach aphid Myzus persicae var. nicotianae

Abstract: Entomopathogenic fungi can adopt an endophytic lifestyle and provide protection against insect herbivores and plant pathogens. So far, most studies have focused on Beauveria bassiana to increase plant resistance against abiotic and biotic stresses, while only little is known for other entomopathogenic fungi. In this study, we investigated whether root inoculation of sweet pepper (Capsicum annuum L.) by the entomopathogenic fungi Akanthomyces muscarius ARSEF 5128 and B. bassiana ARSEF 3097 can improve resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 68 publications
0
32
1
Order By: Relevance
“…, 2013; Wilberts et al. , 2022). Individuals that had passed a set line in one of the olfactometer arms (1 cm from the Y‐junction) at the time of evaluation were considered to have chosen the odor source presented by that olfactometer arm (Goelen et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2013; Wilberts et al. , 2022). Individuals that had passed a set line in one of the olfactometer arms (1 cm from the Y‐junction) at the time of evaluation were considered to have chosen the odor source presented by that olfactometer arm (Goelen et al.…”
Section: Methodsmentioning
confidence: 99%
“…Olfactory response was evaluated 10 min after parasitoid or hyperparasitoid release (Goelen et al, 2020a), or 20 min after aphid release, which was found to be the optimal time point of evaluation in preliminary experiments. Although different set-ups can be used to assess the olfactory behavior of aphids, previous studies have identified glass Y-tubes to not only be suited to assess the olfactory response of primary and secondary parasitoids, but also aphids (Fernández-Grandon et al, 2013;Wilberts et al, 2022). Individuals that had passed a set line in one of the olfactometer arms (1 cm from the Y-junction) at the time of evaluation were considered to have chosen the odor source presented by that olfactometer arm (Goelen et al, 2020a).…”
Section: Olfactometer Bioassaysmentioning
confidence: 99%
“…In addition, an increasing number of studies have reported the potential of endophytic entomopathogenic fungi to induce plant resistance against pathogens and insect herbivores 14,20,22–24 . These indirect effects on insect herbivores may result from the induction of toxic and deterrent plant metabolites, leading to impaired herbivore performance and reduced feeding damage, respectively 14,16,23,25–27 . Endophytic entomopathogenic fungi can also protect plants against insect herbivores directly, when they colonize plants systematically and fungal propagules are ingested by the herbivores, resulting in mycosis 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Given that endophytic entomopathogenic fungi can alter emissions of plant VOCs, 26,33 parasitoids could also be impacted by the inoculation of endophytic entomopathogenic fungi by modulating their attraction towards host‐infested plants. However, there is limited information describing the impact of endophytic entomopathogenic fungi on higher trophic levels, such as parasitoids, and the few studies conducted so far have only investigated effects on parasitoid life history 34–36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation